2009
DOI: 10.1002/mpr.276
|View full text |Cite
|
Sign up to set email alerts
|

Computerized ambulatory monitoring in psychiatry: a multi‐site collaborative study of acceptability, compliance, and reactivity

Abstract: Computerized ambulatory monitoring overcomes a number of methodological and conceptual challenges to studying mental disorders, however concerns persist regarding the feasibility of this approach with severe psychiatric samples and the potential of intensive monitoring to influence data quality. This multi-site investigation evaluates these issues in four independent samples. Patients with schizophrenia (n = 56), substance dependence (n = 85), anxiety disorders (n = 45), and a non-clinical sample (n = 280) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 53 publications
15
104
0
1
Order By: Relevance
“…These findings are similar to compliance rates observed in nonclinical samples. 17 Importantly, the frequency of missing data in this sample was not associated with time in study. The participants required less time to complete electronic interviews as the study progressed, and, with the exception of changes in sad mood, the intensity of daily life variables did not vary as a function of time.…”
Section: Statistical Analyses Data Were Analyzed Using Hierarchicalmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings are similar to compliance rates observed in nonclinical samples. 17 Importantly, the frequency of missing data in this sample was not associated with time in study. The participants required less time to complete electronic interviews as the study progressed, and, with the exception of changes in sad mood, the intensity of daily life variables did not vary as a function of time.…”
Section: Statistical Analyses Data Were Analyzed Using Hierarchicalmentioning
confidence: 97%
“…18 An additional consideration is that the assessment schedule was limited to 5 assessments per day over a 1-week period. Although this schedule is among the most frequently applied, 17 different assessment rhythms may be appropriate as a function of the nature of participating samples. It is also possible that some patients received assistance in responding despite being instructed to complete the daily assessments independently.…”
Section: Statistical Analyses Data Were Analyzed Using Hierarchicalmentioning
confidence: 99%
“…The assessment times were fixed for each participant but randomized across participants. Investigation of fatigue effects and reactivity to the ambulatory methodology using this specific protocol revealed no correlation of time in the study with missing data or with the frequency or intensity of variables, 24 and no participant indicated that they changed their usual activities due to PDA use. The signals occurred within each of the following time periods: 9:00 AM to 12:00 noon; 12:00 noon to 3:00 PM; 3:00 PM to 6:00 PM; and 6:00 PM to 9:00 PM.…”
Section: Participantsmentioning
confidence: 99%
“…21 Computerized ESM uses handheld computers such as personal digital assistants (PDAs), which provide signaling, responding, and data storage through a single device. Studies have recently shown that computerized ESM is a feasible and valid approach to data collection in both hospitalized 22 and community-dwelling 23,24 people with schizophrenia. A major advantage of computerized ESM is that all self-reports are time stamped, enabling researchers to accurately map the sequence of events over a given period of data collection and examine prospective relationships between variables over time within individuals.…”
Section: Predicting Delusional Dimensionsmentioning
confidence: 99%
“…Moreover, EMA also enables data collection at each person's natural environment. Thus, it can reduce bias caused by ambiguous memory, and consequently, it increases the validity level of the assessment [6].…”
Section: Introductionmentioning
confidence: 99%